Yeast mutants temperature-sensitive for growth after random mutagenesis of the chromosomal RAS2 gene and deletion of the RAS1 gene. - Fasano, O (1988)
Saccharomyces cerevisiae strains with a disrupted RAS1 gene and with an intact RAS2 gene (ras1- RAS2 strains) grew well on both fermentable and nonfermentable carbon sources. By constructing isogenic mutants having a disrupted RAS1 locus and a randomly mutagenized chromosomal RAS2 gene, we obtained yeast strains with specific growth defects. The strain TS1 was unable to grow on nonfermentable carbon sources and galactose at 37 degrees C, while it could grow on glucose at the same temperature. The mutated RAS2 gene in TS1 cells encoded a protein with the glycines at positions 82 and 84 replaced by serine and arginine respectively. Both mutations were necessary for temperature sensitivity. We also isolated a mutant yeast that was unable to grow on nonfermentable carbon sources both at 30 and 37 degrees C, while growing on glucose at both temperatures. This phenotype was caused by a single chromosomal mutation, leading to the replacement of aspartic acid 40 of the RAS2 protein by asparagine. A ras1- yeast strain with a chromosomal RAS2 gene harbouring the three mutations together did not grow at any temperature using non-fermentable carbon sources, but it was able to grow on glucose at 30 degrees C, and not at 37 degrees C. The mutated proteins were much less effective than the wild-type RAS2 protein in the stimulation of adenylate cyclase, but were efficiently expressed in vivo. The possible roles of residues 40, 82 and 84 of the RAS2 protein in the regulation of adenylate cyclase are discussed.